The Influence of Chinese Humanistic Spirit on Pakistan, Culture, Economy and Educational System - Himad Ali; Ismail Suardi Wekke (Lingeduca: Journal of Language and Education Studies, 2024)
China has emerged as a soft power in the community of nations, mainly due to its economic development and influences of its humanistic spirit in other countries. By examining, impacts of Chinese humanistic spirit on Pakistani culture, economy and educational system, this paper discussed that how Pakistan culture, economy and educational system was shaped by these influences in different ways and what is the response of Pakistani students and overall nation.  The Chinese government has invested considerably to attract international students, including Pakistani students. This significant contribution of the Chinese government significantly affected Pakistani students in different ways. It allows them to raise their standard of education and to compete with the other nations of the world through their talent and hard work. The paper will discuss in detail the different areas which show improvement, like Natural Sciences, Social Sciences, fields of Technical education and last but not the least the Chinese language program. In Pakistan nowadays, the rising demand for learning the Chinese language is becoming a favourite trend in the younger generations, and this shows how Pakistani people valued Chinese Culture and traditions. This paper will also suggest ways and means how to improve this cultural and educational connectivity further. The main aim should be to use this contribution to strengthen the brotherly relations of the two countries further and to contribute and help the Chinese government in their dream project of One Belt one Road (OBR), which is the best practical example set by Chinese nation and government that they valued to serve the humanity.